Do Online Career Counseling Interventions Work? A Meta-Analysis of Career-Related Psychological Outcomes - Yigit, Busra; Uygun, Ezgi Guney; Erus, Seher Merve (SAGE PUBLICATIONS INC, 2026)
This meta-analysis examined the effectiveness of online career counseling interventions on career-related psychological outcomes. Fourteen studies (N = 1,721) published between 2016 and 2025 and using experimental, quasi-experimental, and pre-experimental designs were synthesized with a random-effects model. Effect sizes were calculated as Hedges's g. Heterogeneity was assessed using Cochran's Q and the I2 index, and publication bias was examined through funnel plots, Fail-safe N, and Duval and Tweedie's trim-and-fill procedure. Results revealed a large overall effect (Hedges's g = 1.650, 95% CI [1.171, 2.130]), indicating that online career counseling significantly improves outcomes such as career adaptability, career decision-making self-efficacy, job search self-efficacy, career confidence, career decision status, perceived employability, career calling, career development, and career awareness. Moderator analyses showed that cultural orientation and number of sessions explained variability in effect sizes, with stronger effects observed in collectivist contexts and in briefer interventions (6 or fewer sessions). Overall, findings suggest that online career counseling is a promising approach for enhancing career-related psychological development. However, substantial heterogeneity highlights the need for more rigorous comparative research to clarify the conditions under which these interventions are most effective.
Keywords: career; online career counseling; intervention; experimental; meta-analysis; FORM PSYCHOMETRIC PROPERTIES; SCALE; LIFE; ADAPTABILITY; INTERESTS; CONSTRUCTION; AMERICAN; CHOICE; BIAS; Psychology